Effects of Fe and Zn Additions on Microstructure and Mechanical Properties of Al–10Si–Mg Alloy - Zengshuo Zhang; Pengfei Ren; Wenxue Fan; Zhuo Zhang; Wei Yu; Hai Hao; Yu Bai; Xianming Meng (Metals)
Based on the idea of integrated computational materials Engineering (ICME), this research applies a digital integrated computing platform integrating ProCAST and MATLAB software. The effects of Fe and Zn contents on the microstructure and properties of die-casting Al–10Si–Mg alloy was investigated through numerical simulation and experimental characterization. The results show that with Fe and Zn contents of 1.30 and 0.25 wt.%, respectively, the grain size and porosity of the die-cast parts are the smallest, and the yield strength and tensile strength are 203 MPa and 313 MPa, respectively. Compared with the addition of 0.14 wt.% Fe and 0.01 wt.% Zn, the increase was 16% and 15.5%, respectively. When the Fe content is higher than 1.30 wt.%, the size of the β-Al5FeSi phase in the alloy matrix increases. Moreover, as the Fe content increases, the morphology of the β-Al5FeSi transforms from elongated to a needle-like shape, which increases brittleness and reduces elongation, tensile strength, and yield strength. When 0.25 wt.% Zn is added, the segregation phenomenon of eutectic Si in the Al–10Si–Mg alloy is inhibited and the tensile strength and yield strength are improved. However, with the increase in Zn content to 0.95 wt.%, there is the coarsening of eutectic Si, resulting in a decreased elongation and decreased mechanical properties. The optimization method of the integrated computing platform greatly simplifies the computing cycle and improves work efficiency.